Abordagem experimental com o uso de biogás proveniente de casca de produtos naturais - Rocha, Leandra Protázio da (Brasil, 2021)
Studies developed in the area of Biology and Chemistry teaching always point out the need for the teacher to articulate the contents worked in the classroom with the students' daily experiences so that learning can actually occur and the use of experimentation is often presented as alternative that enables such a process. Thus, the main objective of this work was to enable meaningful learning through the experimental approach in the production of biogas. The work was carried out with students of the 2nd year of high school, afternoon shift at the State School Maria Almeida do Nascimento in the city of Coari, as part of the pedagogical residency program of the Degree in Sciences: Biology and Chemistry at the Federal University of Amazonas. The experiment consisted of making a biodigester for biogas generation, the theoretical contents about the experiment were worked on. An initial questionnaire was applied related to the students' previous knowledge about the experiment and a final questionnaire, where it was verified that this work promoted an effective learning in the assimilation of the contents by the students. That said, it was observed that the experimentation approach favored the participation of students in the proposed activities, enabling the articulation of theory with practice.